Relationship between dyslipidemia and diabetic retinopathy in type II diabetic patients: A case-control study in Peru - Paucar-Huamani, Milssa (2023)
Background: Diabetic retinopathy (DR) is a primarily asymptomatic microvascular complication. Even though it is preventable, it is the first cause of irreversible blindness among working-age adults. Due to recent meta-analysis results, dyslipidemia is an inconclusive risk factor; therefore, the importance of accomplishing our study in the Peruvian population. Objective: Evaluate the relationship between dyslipidemia and DR in type II diabetic patients of the Ophthalmology area from the Edgardo Rebagliati Martins National Hospital in Lima-Peru, from 2018 to 2020. Methods:  Case-control study, 219 cases and 219 controls were included. Diabetic patients will be classified based on the presence or absence of DR lesions on the ocular fundus determined by the specialist. Lipids parameters (triglyceride, LDL, HDL, total cholesterol) and other variables were recollected and analyzed in STATA 14. Multivariate logistic regression was used to obtain a crude and adjusted Odds Ratio. Results: Dyslipidemia (OR 2.7, p=0.03), elevated triglycerides (OR 1.0044, p=0.03), and low HDL cholesterol (OR 2.16, p=0.03) were significantly associated with DR. Conclusion: Dyslipidemia is an independent risk factor for DR in type II diabetic patients. This result emphasizes the importance of evaluating a lipid panel in diabetic patients.